Alkali activated slag binder composition and its application
By using alkali-excited slag binding material composition in TBM tunnel engineering, the problem of low compressive strength in the prior art is solved, high strength performance under high moisture content and humidity conditions is achieved, meeting the tunnel opening requirements, and reducing the need for lowering cost and environmental impact.
Patent Information
- Application Number
- CN202411333519.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The paving material composition used in the existing TBM tunnel road base is difficult to show high early and later compressive strength under high moisture content and ambient humidity conditions, and cannot meet the requirements of tunnel opening as soon as possible.
Provide an alkali-excited slag binding material composition, including waste stone material, alkali-excited slag gelling material and mixed water, to achieve high strength and good mechanical properties through reasonable proportions, and to accelerate water by using alkaline exciters and water reducers , optimize the hydration process, reduce material costs, and improve resource utilization efficiency.
Under high moisture content and humidity conditions, the early and later compressive strength of the alkali-activated slag binding material composition has been significantly improved, which shortens the maintenance time, meets the tunnel opening requirements, and reduces material costs and environmental impact.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of road engineering, and in particular to an alkali-activated slag binder composition and application thereof. Background Art
[0002] Full-face hard rock tunnel boring machines (TBMs) are often used in tunnel projects with relatively good geological conditions, moderate rock hardness, long tunnel lengths, and high construction progress and precision requirements. They are usually composed of cutterheads, shields, propulsion systems, support systems, slag removal systems, control systems, and other parts. According to different geological conditions and engineering requirements, TBMs can be divided into different types, such as open TBMs and shield TBMs. With the continuous development of transportation infrastructure construction and deep-buried mineral resource development, TBM tunnel projects are increasing. The roads in TBM tunnels are an important guarantee for the efficient transportation of personnel and materials and the dispatch of mechanical equipment. The environment in TBM tunnels is relatively special, with high humidity and limited working space, which puts higher requirements on the performance of road base binders. On the one hand, new base materials need to shorten the maintenance time and form strength as soon as possible to meet the requirements of tunnel opening. In addition, under the concept of environmental protection and sustainable development, new base materials need to consider resource utilization efficiency and environmental impact, and try to use waste rocks generated during TBM tunneling. However, due to the relatively slow early strength development of traditional base binders and long curing time, the performance of traditional inorganic binders is often significantly affected when the moisture content changes, such as reduced strength and poor stability.
[0003] For example, the Chinese patent application 202310276924.3 uses shield slag, gelling components, alkali-activated components, early strength components, and water-retaining healing components to solve the problems of insufficient water stability, easy water loss and cracking, high carbon emissions, limited application scenarios, and insufficient utilization in the process of resource utilization of shield slag. The patent application document with application number 202211024437 discloses a preparation method for a new type of slag filler used for pipeline backfilling. The process is easy to control and greatly reduces the production cost of slag backfilling fillers; the patent application document with application number 202210785859 discloses a lightweight thermal insulation material and its preparation method and application, using blast furnace slag, fly ash, and industrial by-product gypsum to synergistically modify shield slag to obtain a lightweight thermal insulation material with good thermal insulation performance and high compressive strength. However, the application of TBM tunnel excavation waste rock as a binder for the road base in the tunnel lacks specificity. The current binder composition still has the disadvantages of low early strength and the strength growth being greatly affected by changes in water content, which cannot meet the requirements of opening to traffic as soon as possible during tunnel excavation.
[0004] Based on this, how to provide a binder composition that can maintain high early compressive strength and late compressive strength after curing under conditions of high moisture content and environmental humidity, so as to be better used as a paving material in TBM tunnel road base, is one of the important technical problems that need to be solved in this field. Summary of the invention
[0005] The main purpose of the present invention is to provide an alkali-activated slag binder composition and its application, so as to solve the problem that the paving material composition used for TBM tunnel road base in the prior art is difficult to show high early strength and late strength after curing under conditions of high moisture content and environmental humidity.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides an alkali-activated slag binder composition, which includes waste stone, alkali-activated slag cementitious material and mixing water; based on the total weight of the waste stone and the alkali-activated slag cementitious material as 100%, the content of mixing water is 9%~13%; in parts by weight, the alkali-activated slag cementitious material includes: 50~80 parts of slag powder, 0.5~20 parts of cement, 0.1~2 parts of cement early strength agent, 4~10 parts of alkaline activator and 0.15~3 parts of water reducer.
[0007] Furthermore, the weight ratio of waste rock to alkali-activated slag cementitious material is (1.5~4.0):1.
[0008] Furthermore, the alkali-activated slag cementitious material includes, by weight: 60-80 parts of slag powder, 5-20 parts of cement, 0.2-2 parts of cement early strength agent, 5-10 parts of alkaline activator and 0.2-2.5 parts of water reducing agent.
[0009] Furthermore, the slag powder is S95 grade slag powder, preferably S95 grade slag powder obtained by drying and grinding blast furnace water-quenched slag; and / or, the cement is selected from one or more of 32.5 grade ordinary Portland cement, 42.4 grade ordinary Portland cement and 52.5 grade ordinary Portland cement, preferably 42.4 grade ordinary Portland cement; and / or, the cement early strength agent is calcium chloride and / or calcium formate; and / or, the alkaline activator is selected from at least two of sodium carbonate, quicklime, calcium hydroxide, magnesium oxide and magnesium hydroxide; and / or, the water reducer is selected from one or more of lignin sulfonate water reducers, naphthalene water reducers and polycarboxylic acid powder water reducers, preferably polycarboxylic acid powder water reducers.
[0010] Furthermore, the alkaline activator is selected from: a mixture of sodium carbonate and quicklime, and the weight ratio of sodium carbonate to quicklime is (1:2) to (2:1); or, a mixture of sodium carbonate and calcium hydroxide, and the weight ratio of sodium carbonate to calcium hydroxide is (2:3) to (3:2); or, a mixture of calcium hydroxide and magnesium oxide, and the weight ratio of calcium hydroxide to magnesium oxide is (1:2) to (2:1); or, a mixture of sodium carbonate and magnesium hydroxide, and the weight ratio of sodium carbonate to magnesium hydroxide is (1:2) to (2:1) One or more.
[0011] Furthermore, the weight ratio of cement to slag powder is (15~30):68.
[0012] Furthermore, the weight ratio of cement early strength agent to slag powder is (1.0~1.2):68.
[0013] Furthermore, the weight ratio of the alkaline activator to the slag powder is (8~12):68.
[0014] Furthermore, the waste stone includes gravel and stone powder, and the weight ratio of gravel to stone powder is (1.8~2.0):1.
[0015] Furthermore, the particle size of the stone is 5mm~40mm, and the particle size of the stone powder is 1mm~5mm.
[0016] The second aspect of the present invention provides a use of the above-mentioned alkali-activated slag binder composition as a road paving material in the field of full-section hard rock tunnel boring machine tunnel engineering.
[0017] Furthermore, the waste rock and alkali-activated slag cementitious material in the alkali-activated slag binder composition are mixed with mixing water and then paved.
[0018] By applying the technical solution of the present invention, an alkali-activated slag binder composition is provided, which not only realizes the rational utilization of waste stone, reduces its environmental impact, but also reduces the material cost by reasonably mixing waste stone, alkali-activated slag cementitious material and mixing water. At the same time, due to the special alkali-activated slag cementitious material component, the composition exhibits good mechanical properties and durability at a high water content after solidification. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0020] As described in the background art, the paving material composition used in the TBM tunnel road base in the prior art has the problem that it is difficult to show high early strength and late strength after curing under conditions of high moisture content and environmental humidity. In order to solve the above technical problems, the first aspect of the present invention provides an alkali-activated slag binder composition, which includes waste stone, alkali-activated slag cementitious material and mixing water; based on the total weight of waste stone and alkali-activated slag cementitious material as 100%, the content of mixing water is 9%~13%; by weight, the alkali-activated slag cementitious material includes: 50~80 parts of slag powder, 0.5~20 parts of cement, 0.1~2 parts of cement early strength agent, 4~10 parts of alkaline activator and 0.15~3 parts of water reducer.
[0021] The alkali-activated slag binder composition provided by the present invention contains waste stone, alkali-activated slag cementitious material and a specific content of mixing water. The waste stone serves as a reinforcing phase in the subsequent solidification process, and then plays a cementing and filling role in the composition slurry. The alkali-activated slag cementitious material can form a cementing system with high density and high cross-linking degree, and effectively cement the waste stone to achieve solidification and obtain a high-strength stone body, thereby solving the problem of low strength and poor cementing degree of traditional TBM pavement paving materials. Specifically, in the alkali-activated slag cementitious material, slag micropowder provides the main potential hydraulic mineral components, the clinker component in the cement serves as a supplement to the hydraulic minerals, the alkaline activator provides the alkaline environment and alkali metal ions required for the dissolution and hydration of the potential hydraulic mineral components, and the gypsum, calcium oxide, magnesium oxide and sodium oxide in the cement can serve as a supplement to the alkaline activator. The alkaline activator destroys the glassy structure of the slag, dissolves the silicon, aluminum and other elements therein and undergoes a polymerization reaction to form a product with cementing properties. Alkali activators can also promote the potential activity in slag and accelerate the process of hydration reaction. Cement early strength agent can accelerate the early hydration reaction of cement and slag and promote the development of early strength. Its mechanism of action includes promoting the dissolution of cement clinker minerals, accelerating the formation rate of hydration products, refining the microstructure of cement stone, etc., thereby providing more favorable conditions for the subsequent hydration of slag. The main function of the water reducer is to disperse cement and slag particles, reduce the agglomeration between particles, improve the uniformity of the hydration reaction of the alkali-activated slag binder in the present invention, and reduce the formation of pores and defects. At the same time, the water reducer can also improve the dispersion uniformity of each component in the binder, make up for the defect of uneven mixing in the limited space of the tunnel, and have a positive effect on the working performance of the binder. The alkali-activated slag cementitious material provided by the present invention includes the above three (i.e., alkali activator, early strength agent, and water reducer) at the same time. The synergistic effect of the three can more significantly optimize the hydration process of slag, reduce water consumption, and improve the overall performance of the material, so that the alkali-activated slag binder has excellent characteristics such as high early strength, early strength development is less affected by changes in moisture content, and short curing time.
[0022] In particular, in the alkali-activated slag binder composition provided by the present invention, its water content is strictly controlled, that is, based on the total weight of waste stone and alkali-activated slag cementitious material as 100%, the content of mixing water is 9% to 13%. This is because as the water content increases, the hydration reaction process of the cementitious material is promoted more fully, and the later strength is higher. However, too high a water content will affect the curing effect of the early material, and then affect its application effect, and cannot meet the requirements for the early opening of the tunnel. Based on this, the inventors have optimized the water content of the system containing waste stone and alkali-activated slag cementitious material through a large number of experiments, and obtained the relative content of the above-mentioned mixing water, and successfully achieved the preparation of an alkali-activated slag binder composition with excellent performance within this dosage range, which exhibits high early and late compressive strength after curing.
[0023] In order to further improve resource utilization and product added value of the obtained alkali-activated slag binder composition, the waste rock is preferably waste rock generated by TBM tunneling, thereby realizing on-site utilization of tunneling waste rock, reducing the procurement and transportation costs of raw materials, and greatly reducing the transportation costs and environmental pressure of waste rock. In practical applications, waste rock is mainly composed of rock fragments and rock powder, and the types of rocks may include granite, limestone, sandstone, etc.
[0024] Furthermore, after a large number of experiments, the inventors have found that the preferred weight ratio of waste rock to alkali-activated slag cementitious material is (1.5-4.0): 1. The above ratio can not only significantly improve the strength and stability of the alkali-activated slag binder composition after solidification, but also further improve the utilization rate of waste rock.
[0025] In several preferred embodiments, the alkali-activated slag cementitious material includes, by weight: 60-80 parts of slag powder, 5-20 parts of cement, 0.2-2 parts of cement early strength agent, 5-10 parts of alkaline activator and 0.2-2.5 parts of water reducing agent. The inventors have optimized the content of each component in the alkali-activated slag cementitious material through a large number of experiments, and found that when it is within the above range, it can more significantly optimize the hydration process of slag and improve the early strength and late strength of the alkali-activated slag binder composition after curing.
[0026] In several more preferred embodiments, the alkali-activated slag cementitious material includes, by weight: 60-80 parts of slag powder, 5-20 parts of cement, 0.2-2 parts of cement early strength agent, 5-10 parts of alkaline activator and 0.2-2.0 parts of water reducing agent. The inventor further optimized the content of each component in the alkali-activated slag cementitious material through a large number of experiments to obtain the above dosage range. At this time, the alkali-activated slag binder composition shows better early strength and late strength after curing.
[0027] Furthermore, the slag powder is S95 grade slag powder, preferably S95 grade slag powder obtained by drying and grinding blast furnace water-quenched slag; and / or, the cement is selected from one or more of 32.5 grade ordinary Portland cement, 42.4 grade ordinary Portland cement and 52.5 grade ordinary Portland cement, preferably 42.4 grade ordinary Portland cement; and / or, the cement early strength agent is calcium chloride and / or calcium formate; and / or, the alkaline activator is selected from at least two of sodium carbonate, quicklime, calcium hydroxide, magnesium oxide and magnesium hydroxide; and / or, the water reducer is selected from one or more of lignin sulfonate water reducers, naphthalene water reducers and polycarboxylic acid powder water reducers, preferably polycarboxylic acid powder water reducers. Theoretically, the slag derivatives, cement, lightening activator, cement early strength agent and water reducing agent in the alkali-activated slag cementitious material can all be selected from the types commonly used in the field, as long as the corresponding functions can be achieved. The above types optimized by the inventor after a large number of experiments can be better adapted to the special environment of TBM tunnel engineering, thereby improving the reliability of the alkali-activated slag binder composition in its application.
[0028] Specifically, the lignin sulfonate water reducer is selected from one or more of the common type, slow setting type, and early strength type, and its specific model may be MN-1; the naphthalene water reducer is selected from one or more of the standard type, slow setting type, and early strength type, and its specific model may be FDN-C; the polycarboxylic acid powder water reducer is selected from one or more of the standard type, early strength type, slow setting type, slow release type, and shrinkage reduction type, and its specific model may be TD-JSS.
[0029] And, based on the above alkali-activated slag binder composition with a specific formula, the inventors further preferred the alkaline activator to be selected from: a mixture of sodium carbonate and quicklime, and the weight ratio of sodium carbonate to quicklime is (1:2) to (2:1); or a mixture of sodium carbonate and calcium hydroxide, and the weight ratio of sodium carbonate to calcium hydroxide is (2:3) to (3:2); or a mixture of calcium hydroxide and magnesium oxide, and the weight ratio of calcium hydroxide to magnesium oxide is (1:2) to (2:1); or a mixture of sodium carbonate and magnesium hydroxide, and the weight ratio of sodium carbonate to magnesium hydroxide is (1:2) to (2:1). The above-mentioned specific alkaline activators are all composed of two compounds, and can effectively activate the activity of slag powder, thereby improving the strength and durability of the alkali-activated slag binder composition after solidification.
[0030] Among the above-mentioned alkaline activator raw materials, sodium carbonate is light sodium carbonate (also known as soda ash), and its grade can be superior, first-class or qualified, preferably superior, wherein the total alkali content on a dry basis is not less than 99.2%. The mesh number of quicklime is above 300 mesh, and preferably its calcium content is not less than 90%. The mesh number of calcium hydroxide is above 300 mesh, and preferably its calcium content is not less than 90%. Magnesium oxide can be one or more of light magnesium oxide, light-burned magnesium oxide and building material magnesium oxide, preferably light magnesium oxide. Magnesium hydroxide is type I or type II, preferably type I, wherein the magnesium hydroxide content is not less than 95%.
[0031] In order to make better use of the clinker component C in cement 3 S and C 2 The hydrated calcium silicate gel (CSH) provided by S in the later hydration process can more effectively fill the pores of the alkali-activated slag binder, thereby improving the strength. The preferred weight ratio of cement to slag powder is (15~30):68.
[0032] In order to further balance the early strength and later stability of the alkali-activated slag binder composition and make it more reliable in application, the preferred weight ratio of cement early strength agent to slag powder is (1.0~1.2):68.
[0033] With respect to the alkali-activated slag binder composition provided by the present invention, the alkaline activator therein can improve the early strength of the composition after solidification. When the content of the alkaline activator is too high, the reaction speed will be too fast, resulting in an increase in the internal structural defects of the sample, thereby reducing the later strength. Therefore, after a large number of experiments, the inventors preferably selected a weight ratio of the alkaline activator to the slag powder of (8~12):68, and obtained an alkali-activated slag binder composition with higher early and later strengths after solidification within this ratio relationship.
[0034] Furthermore, in order to enhance the structural reinforcement effect of waste stone on the material obtained after solidification and achieve higher early and late strength performance, it is preferred that the waste stone includes gravel and stone powder, and the weight ratio of gravel to stone powder is (1.8~2.0):1.
[0035] Furthermore, after a large number of experiments, the inventors have preferably selected the stone particle size of 5mm~40mm and the stone powder particle size of 1mm~5mm, and through the above-mentioned optimization of the particle size of the waste stone, the alkali-activated slag binder composition exhibits higher strength and stable reliability after solidification.
[0036] A second aspect of the present invention provides a use of the above-mentioned material as a road paving material in the field of full-face hard rock tunnel boring machine tunnel engineering.
[0037] The above-mentioned alkali-activated slag binder composition provided by the present invention not only has the characteristics of high early strength and stable later strength after solidification, but the solidified material after rolling molding can reach more than 1Mpa within 4 hours and more than 2.5Mpa within 8 hours. After 4 hours of curing, it can meet the requirements for TBM tunnel opening, thereby significantly improving the efficiency of TBM tunnel excavation construction.
[0038] Furthermore, the waste rock and alkali-activated slag cementitious material in the alkali-activated slag binder composition are mixed with mixing water and then paved.
[0039] And, in practical application, the construction process and requirements are as follows:
[0040] (1) Use a mixer to mix the waste rock and alkali-activated slag materials according to the proportion, pack them into bags and transport them to the TBM tunnel;
[0041] (2) Use the TBM slag transport system (slag bucket or slag truck or belt conveyor or scraper conveyor) to transport solid raw materials from the excavation section to the road paving location;
[0042] (3) Alkali-activated slag cementitious material and waste rock are mixed evenly to obtain a binder. The mixing can be done by a small mixer or a small excavator, preferably a small mixer. The mixing process is mainly mechanical, supplemented by manual labor. The material is spread as it is mixed, and the spreading and rolling should be completed within 3 hours after adding mixing water. A 100-200 m test section should be made before full spreading and rolling.
[0043] (4) During the mixing process, add mixing water in small amounts and multiple times. The mixing water can be the seepage water intercepted in the tunnel. When the water source is insufficient, the drainage system or pipeline in the tunnel can be used to introduce water from outside the tunnel.
[0044] (5) Use an excavator to evenly spread the binder to the bottom of the TBM tunnel, spread and compact it in layers, and the thickness of the loose paving should be 200~400mm; before spreading and rolling the next layer, sprinkle water on the surface of the previous layer until the surface is moist;
[0045] (6) Use a small vibratory roller to roll and compact the material layer by layer, with the rolling times not less than 4 times. The size of the roller can be selected based on the size of the TBM tunnel space and the layout of other ancillary facilities in the tunnel.
[0046] For smaller TBM tunnels (usually around 3-6 meters in diameter):
[0047] Roller: A small walk-behind roller can be used, and the working mass is usually between 1 and 3 tons.
[0048] Excavator: A small or micro excavator can be used. The weight of the whole machine may be around 1 to 10 tons, and the bucket capacity is generally 0.1 to 0.5 cubic meters.
[0049] For medium-sized TBM tunnels (about 6-10 meters in diameter):
[0050] Roller: A medium-sized self-propelled roller is more suitable, with a working mass of approximately 3 to 12 tons.
[0051] Excavator: Medium-sized excavators are more suitable, with a total machine weight of 10 to 30 tons and a bucket capacity of 0.5 to 1.5 cubic meters.
[0052] For larger size TBM tunnels (greater than 10m diameter):
[0053] Road roller: Large self-propelled road roller with a working mass of more than 12 tons.
[0054] Excavator: Large excavator, with a total weight of more than 30 tons and a bucket capacity of more than 1.5 cubic meters.
[0055] (7) Watering maintenance is carried out for no less than 4 hours to finally form the TBM tunnel road base structure.
[0056] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0057] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0058] Example 1
[0059] A method for preparing an alkali-activated slag binder composition:
[0060] The materials used in this embodiment are:
[0061] Waste rock: 4454g TBM tunnel excavation waste rock, consisting of gravel with a particle size of 5mm~40mm and stone powder with a particle size of 1mm~5mm, with a mass ratio of 2:1. The maximum particle size of the waste rock obtained does not exceed 40mm.
[0062] Alkali-activated slag cementitious material: a total of 1113g, of which S95 grade slag powder accounts for 68%, PO 42.5 cement accounts for 20%, cement early strength agent calcium chloride accounts for 1%, alkaline activator mixed with sodium carbonate and quicklime in a mass ratio of 1:1 accounts for 10%, and early strength polycarboxylate water reducer TD-JSS accounts for 1%. In addition, the weight ratio of cement to slag powder is 20:68; the weight ratio of cement early strength agent to slag powder is 1:68; the weight ratio of alkaline activator to slag powder is 10:68.
[0063] That is, the weight ratio of waste rock to alkali-activated slag cementitious material is 4:1, and 10% of mixing water is added based on the sum of the weights of the two being 100%.
[0064] The preparation method is as follows: according to the above formula, the alkali-activated slag cementitious material and the waste stone are uniformly mixed, and mixing water is gradually added during the mixing process, and the mixing time is not less than 90s to prepare the alkali-activated slag binder composition.
[0065] Example 2
[0066] A method for preparing an alkali-activated slag binder composition:
[0067] The difference between this embodiment and embodiment 1 is the amount of mixing water added. Specifically, based on the sum of the weight of the waste rock and the alkali-activated slag cementitious material being 100%, 11% of mixing water is added.
[0068] Example 3
[0069] A method for preparing an alkali-activated slag binder composition:
[0070] The difference between this embodiment and embodiment 1 is the amount of mixing water added. Specifically, based on the sum of the weight of the waste rock and the alkali-activated slag cementitious material being 100%, 12% of mixing water is added.
[0071] Example 4
[0072] A method for preparing an alkali-activated slag binder composition:
[0073] The difference between this embodiment and embodiment 1 is the amount of mixing water added. Specifically, based on the sum of the weight of the waste rock and the alkali-activated slag cementitious material being 100%, 13% of mixing water is added.
[0074] Example 5
[0075] A method for preparing an alkali-activated slag binder composition:
[0076] The only difference between this embodiment and embodiment 1 is that in the alkali-activated slag cementitious material, the proportion of the alkaline activator is changed to 5%, and the proportion of S95 grade slag powder is changed to 73%, that is, the weight ratio of the alkaline activator to the slag powder is changed to 4.7:68. The proportions of other components remain unchanged.
[0077] Example 6
[0078] A method for preparing an alkali-activated slag binder composition:
[0079] The only difference between this embodiment and embodiment 1 is that in the alkali-activated slag cementitious material, the proportion of the alkaline activator is changed to 15%, and the proportion of the S95 grade slag powder is changed to 63%, that is, the weight ratio of the alkaline activator to the slag powder is changed to 16.2:68. The proportions of other components remain unchanged.
[0080] Example 7
[0081] A method for preparing an alkali-activated slag binder composition:
[0082] The only difference between this embodiment and embodiment 1 is that the proportion of cement in the alkali-activated slag cementitious material is changed to 10%, and the proportion of S95 grade slag powder is changed to 78%, that is, the weight ratio of cement to slag powder is changed to 8.7:68. The proportions of other components remain unchanged.
[0083] Example 8
[0084] A method for preparing an alkali-activated slag binder composition:
[0085] The only difference between this embodiment and embodiment 1 is that the proportion of cement in the alkali-activated slag cementitious material is changed to 40%, and the proportion of S95 grade slag powder is changed to 48%, that is, the weight ratio of cement to slag powder is changed to 56.7:68. The proportions of other components remain unchanged.
[0086] Example 9
[0087] A method for preparing an alkali-activated slag binder composition:
[0088] The only difference between this embodiment and embodiment 1 is that in the alkali-activated slag cementitious material, the proportion of cement early strength agent is changed to 0.5%, and the proportion of S95 grade slag powder is changed to 68.5%, that is, the weight ratio of cement early strength agent to slag powder is changed to 0.5:68. The proportions of other components remain unchanged.
[0089] Example 10
[0090] A method for preparing an alkali-activated slag binder composition:
[0091] The only difference between this embodiment and embodiment 1 is that in the alkali-activated slag cementitious material, the proportion of cement early strength agent is changed to 2%, and the proportion of S95 grade slag powder is changed to 67%, that is, the weight ratio of cement early strength agent to slag powder is changed to 2.0:68. The proportions of other components remain unchanged.
[0092] Embodiment 11
[0093] A method for preparing an alkali-activated slag binder composition:
[0094] The only difference between this embodiment and embodiment 1 is that the total weight of the waste rock is changed to 3897g, and the total weight of the alkali-activated slag cementitious material is changed to 1670g, that is, the weight ratio of the waste rock and the alkali-activated slag cementitious material is changed to 7:3; the proportion of each component in the two remains unchanged.
[0095] Example 12
[0096] A method for preparing an alkali-activated slag binder composition:
[0097] The only difference between this embodiment and Embodiment 1 is that the total weight of waste rock is changed to 3340 g, and the total weight of alkali-activated slag cementitious material is changed to 2227 g, that is, the weight ratio of waste rock and alkali-activated slag cementitious material is changed to 1.5:1; the proportion of each component in the two remains unchanged.
[0098] Embodiment 13
[0099] A method for preparing an alkali-activated slag binder composition:
[0100] The only difference between this embodiment and embodiment 1 is that the total weight of the waste rock is changed to 5010g, and the total weight of the alkali-activated slag cementitious material is changed to 557g, that is, the weight ratio of the waste rock and the alkali-activated slag cementitious material is changed to 9:1; the proportion of each component in the two remains unchanged.
[0101] Embodiment 14
[0102] A method for preparing an alkali-activated slag binder composition:
[0103] The only difference between this embodiment and Embodiment 1 is that the total weight of the waste rock is changed to 2895g, and the total weight of the alkali-activated slag cementitious material is changed to 2894g, that is, the weight ratio of the waste rock and the alkali-activated slag cementitious material is changed to 1:1; the proportion of each component in the two remains unchanged.
[0104] Embodiment 15
[0105] A method for preparing an alkali-activated slag binder composition:
[0106] The only difference between this embodiment and embodiment 1 is that the alkaline activator in the alkali-activated slag cementitious material is changed to an alkaline activator obtained by mixing sodium carbonate and calcium hydroxide in a mass ratio of 1:1.5, and its proportion in the alkali-activated slag cementitious material remains unchanged.
[0107] Example 16
[0108] A method for preparing an alkali-activated slag binder composition:
[0109] The only difference between this embodiment and embodiment 1 is that the alkaline activator in the alkali-activated slag cementitious material is changed to an alkaline activator obtained by mixing calcium hydroxide and magnesium oxide in a mass ratio of 1:1, and its proportion in the alkali-activated slag cementitious material remains unchanged.
[0110] Embodiment 17
[0111] A method for preparing an alkali-activated slag binder composition:
[0112] The only difference between this embodiment and embodiment 1 is that the alkaline activator in the alkali-activated slag cementitious material is changed to an alkaline activator containing only sodium carbonate, and its proportion in the alkali-activated slag cementitious material remains unchanged.
[0113] Embodiment 18
[0114] A method for preparing an alkali-activated slag binder composition:
[0115] The only difference between this embodiment and embodiment 1 is that the alkaline activator in the alkali-activated slag cementitious material is changed to an alkaline activator containing only magnesium hydroxide, and its proportion in the alkali-activated slag cementitious material remains unchanged.
[0116] Embodiment 19
[0117] A method for preparing an alkali-activated slag binder composition:
[0118] The only difference between this embodiment and embodiment 1 is that the mass ratio of stone to stone powder in the waste stone is changed to 1.5:1.
[0119] Embodiment 20
[0120] A method for preparing an alkali-activated slag binder composition:
[0121] The only difference between this embodiment and embodiment 1 is that the mass ratio of stone to stone powder in the waste stone is changed to 2.5:1.
[0122] Comparative Example 1
[0123] A method for preparing an alkali-activated slag binder composition:
[0124] The difference between this comparative example and Example 1 is the amount of mixing water added. Specifically, based on the sum of the weight of the waste rock and the alkali-activated slag cementitious material being 100%, 9% of mixing water is added.
[0125] Comparative Example 2
[0126] A method for preparing an alkali-activated slag binder composition:
[0127] The difference between this comparative example and Example 1 is the amount of mixing water added. Specifically, based on the sum of the weight of the waste rock and the alkali-activated slag cementitious material being 100%, 14% of mixing water is added.
[0128] Comparative Example 3
[0129] A method for preparing an alkali-activated slag binder composition:
[0130] The only difference between this comparative example and Example 1 is that the alkali-activated slag cementitious material does not include an alkaline activator.
[0131] Comparative Example 4
[0132] A method for preparing an alkali-activated slag binder composition:
[0133] The only difference between this comparative example and Example 1 is that the alkali-activated slag cementitious material does not include cement.
[0134] Comparative Example 5
[0135] A method for preparing an alkali-activated slag binder composition:
[0136] The only difference between this comparative example and Example 1 is that the alkali-activated slag cementitious material does not include a cement early strength agent.
[0137] Comparative Example 6
[0138] A method for preparing an alkali-activated slag binder composition:
[0139] The only difference between this comparative example and Example 1 is that only 1113 g of cement is used as the alkali-activated slag cementitious material.
[0140] Test Method
[0141] The alkali-activated slag binder obtained from the above embodiments and comparative examples was placed in a cylindrical test mold (diameter × height of 150 mm × 150 mm), and compacted by a press. The pressure drop rate was controlled at 1 mm / min, the static pressure reached 400 KN, and the static pressure time was not less than 1 min. After static pressure molding, demoulding was performed and the binder was placed in a curing box for curing. At curing times of 2 h, 4 h, 8 h, and 7 d, the compressive strength was tested according to the "Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTG E51). The results are shown in Table 1.
[0142] Table 1
[0143]
[0144] Application Example 1
[0145] Field test of alkali activated slag binder composition as road paving material in TBM tunnel engineering field:
[0146] (1) Taking Example 1 as an example, a mixer is used to process waste rock and alkali-activated slag materials according to the above ratio, and then bag them and transport them to the TBM tunnel;
[0147] (2) The belt of the belt conveyor is directly unloaded onto the surface to be paved;
[0148] (3) Use small excavators for paving and mixing;
[0149] (4) The rolling shall be carried out by a 3t vibratory roller and the number of rolling passes shall be no less than 5 times;
[0150] (5) Sprinkle water to maintain moisture for 4 hours;
[0151] Test results:
[0152] The road can be opened to traffic after 4 hours of curing; the compaction degree is 94% after inspection, and the 7d unconfined compressive strength is 16.2Mpa.
[0153] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the preparation of an alkali-activated slag binder composition with excellent performance and low cost. When it is used as a road paving material in TBM tunnel engineering, it exhibits high early and late compressive strength even under high moisture content conditions.
[0154] Specifically:
[0155] Comparing Examples 1 to 4 and Comparative Examples 1 and 2, it can be seen that as the moisture content increases between 9% and 14%, the 2h compressive strength decreases slightly, which is mainly because the increase in moisture content slows down the setting time of the cementitious material and the compaction of the material; while the 4h compressive strength does not decrease significantly, and is maintained above 1Mpa, which shows that the alkali-activated slag binder has the characteristic that the early strength is less affected by the change in moisture content, and the later strength shows an upward trend, mainly because as the moisture content increases, the hydration reaction process of the cementitious material is promoted more fully, so the greater the moisture content, the higher the later strength. However, in Comparative Example 2, although its 7d compressive strength is as high as 20MPa, its 4h strength is almost non-existent, which cannot meet the requirements for the tunnel to be opened to traffic as soon as possible.
[0156] By comparing Example 1, Example 5, Example 6 and Comparative Example 3, it can be seen that as the ratio of alkaline activator to S95 grade slag powder increases, the early (2h, 4h, 8h) strength increases, but when the ratio of the two exceeds 10:68 and the alkaline activator is excessive, the later (7d) strength decreases. This shows that increasing the alkaline activator content appropriately can improve the early strength of the test block. However, when the alkaline activator content is too high, the reaction speed will be too fast, resulting in an increase in the internal structural defects of the sample, thereby reducing the later strength.
[0157] Comparing Example 1, Example 7, Example 8 and Comparative Example 4, it can be seen that with the increase of cement content and the decrease of slag powder content, the early strength of the sample decreases, but the later strength increases. However, when the cement content increases to a certain extent, the later strength of the sample also decreases, such as in Examples 7 and 8. This is because the appropriate amount of cement content can provide power for the later strength, which is because the clinker component C in cement 3 S and C 2 In the later hydration process, more calcium silicate hydrate gel (CSH) is produced, which can fill the pores of alkali-activated slag binder, making the structure denser and improving the strength. However, too much cement will cause uneven distribution of hydration products in the system, increase porosity, and weaken the development of later strength.
[0158] Also, in Example 14, the weight ratio of waste rock and alkali-activated slag cementitious material was changed to 1:1, and the compressive strength of the resulting composition was slightly increased after curing. However, the material consumption was greatly increased, resulting in increased costs and difficulty in having practical application value.
[0159] Comparing Example 1, Example 19, and Example 20, it can be seen that increasing the ratio of stone to stone powder is more conducive to early strength. It should be noted that the terms "first", "second", etc. in the specification and claims of this application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0160] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An alkali-activated slag binder composition is used as a road paving material in the field of full-section hard rock tunnel boring machine tunnel engineering, characterized in that: The alkali-activated slag binder composition comprises waste rock, alkali-activated slag cementitious material and mixing water; Based on the total weight of the waste rock and the alkali-activated slag cementitious material as 100%, the content of the mixing water is 9% to 13%; The weight ratio of the waste rock to the alkali activated slag cementitious material is (1.5-4.0): 1; The alkali-activated slag cementitious material comprises, by weight: 50-80 parts of slag powder, 0.5-20 parts of cement, 0.1-2 parts of cement early strength agent, 4-10 parts of alkaline activator and 0.15-3 parts of water reducing agent; The alkaline activator is a mixture of calcium hydroxide and magnesium oxide; or, the alkaline activator is a combination of one or more selected from a mixture of sodium carbonate and quicklime, a mixture of sodium carbonate and calcium hydroxide, and a mixture of sodium carbonate and magnesium hydroxide and the mixture of calcium hydroxide and magnesium oxide; and: In the mixture of calcium hydroxide and magnesium oxide, the weight ratio of calcium hydroxide to magnesium oxide is (1:2) to (2:1); In the mixture of sodium carbonate and quicklime, the weight ratio of the sodium carbonate to the quicklime is (1:2) to (2:1); In the mixture of sodium carbonate and calcium hydroxide, the weight ratio of the sodium carbonate to the calcium hydroxide is (2:3) to (3:2); In the mixture of sodium carbonate and magnesium hydroxide, the weight ratio of the sodium carbonate to the magnesium hydroxide is one or more of (1:2) to (2:1).
2. The use according to claim 1, characterized in that: In parts by weight, the alkali-activated slag cementitious material includes: 60 to 80 parts of the slag powder, 5 to 20 parts of the cement, 0.2 to 2 parts of the cement early strength agent, 5 to 10 parts of the alkaline activator and 0.2 to 2.5 parts of the water reducing agent.
3. The use according to claim 2, characterized in that: The slag powder is S95 grade slag powder; and / or, The cement is selected from one or more of 32.5 grade ordinary Portland cement, 42.4 grade ordinary Portland cement and 52.5 grade ordinary Portland cement; and / or, The cement early strength agent is calcium chloride and / or calcium formate; and / or, The water reducer is selected from one or more of lignin sulfonate water reducers, naphthalene water reducers and polycarboxylic acid powder water reducers.
4. The use according to claim 2, characterized in that: The weight ratio of the cement to the slag powder is (15-30):
68.
5. The use according to claim 2, characterized in that: The weight ratio of the cement early strength agent to the slag fine powder is (1.0-1.2):
68.
6. The use according to claim 2, characterized in that: The weight ratio of the alkaline activator to the slag powder is (8-12):
68.
7. The use according to claim 1, characterized in that: The waste stone includes gravel and stone powder, and the weight ratio of the gravel to the stone powder is (1.8~2.0):
1.
8. The use according to claim 7, characterized in that: The particle size of the stone is 5mm~40mm, and the particle size of the stone powder is 1mm~5mm.
